Dynamic Mechanical Characterization of Polyurethane/Multiwalled Carbon Nanotube Composite Thermoplastic Elastomers. Issue 14 (22nd September 2017) - Mansour, Gabriel; Tsongas, Konstantinos; Tzetzis, Dimitrios; Tzikas, Konstantinos
ABSTRACT: An effective analytical–experimental test method is used in the current work to characterize the vibration isolation behavior of thermoplastic polyurethane multiwalled carbon nanotube nanocomposites with five different concentrations. To determine the static compression stiffness and hysteresis of the specimens, compression and cyclic tests were conducted. The vibration isolation properties were determined through the analysis of transmissibility of a suitably designed test system. Thermoplastic polyurethane's mechanical properties and vibration isolation properties were improved with the addition of multiwalled carbon nanotubes. Considering the obtained results, the dynamic stiffness of thermoplastic polyurethane and its capacity to isolate vibration can be adjusted by controlling the proportion of multiwalled carbon nanotubes. GRAPHICAL ABSTRACT: